Is conscientious objection incompatible with healthcare professionalism?. Issue 3 (3rd July 2019) - Neal, Mary; Fovargue, Sara
Abstract : Is conscientious objection (CO) necessarily incompatible with the role and duties of a healthcare professional? An influential minority of writers on the subject think that it is. Here, we outline the positive case for accommodating CO and examine one particular type of incompatibility claim, namely that CO is fundamentally incompatible with proper healthcare professionalism because the attitude of the conscientious objector exists in opposition to the disposition (attitudes and underlying character) that we should expect from a 'good' healthcare professional. We ask first whether this claim is true in principle : what is the disposition of a 'good' healthcare professional, and how does CO align with or contradict it? Then, we consider practical compatibility, acknowledging the need to identify appropriate limits on the exercise of CO and considering what those limits might be. We conclude that CO is not fundamentally incompatible – either in principle or in practice – with good healthcare professionalism.